Editorial: Social and Environmental Accounting Research (SEA) - A Special Issue? - Cornelia Beck; Sandra van der Laan (Australasian Accounting, Business and Finance Journal, 2008)
For what is now an extended period of time, a number of researchers have been working in what could be described as “an isolated, very small and persecuted community… seeking to reify this mysterious oddity that was social accounting (emphasis in original)” (Gray, 2007, p. 2). However, with increasing commercial and regulatory emphasis globally on environmental degradation and rehabilitation, climate change and the social responsibilities of the corporate world, this isolated, small community has not only gained a voice, but an increased profile and credibility for researchers in the area. As such, social and environmental accounting (SEA) research (as it is now known) boasts both a history and a future as a stand-alone sub-discipline of accounting research. More and more emerging scholars are opting for research programs that encompass or engage with SEA issues. Indeed, many major accounting conferences (such as the European Accounting Association (EAA) and Accounting and Finance Association of Australian and New Zealand (AFAANZ)) offer dedicated SEA streams. SEA is no longer a special issue! But as noted above, this was not always the case…..
Keywords: Editorial; CSEAR; Special Issue; Social and Environmental Accounting